Aproveitamento de resíduos das agroindústrias cervejeira e macaúba para obtenção de farinhas alimentícias e sua utilização em biscoitos tipo cookie - Sayeny de Ávila Gonçalves (2019)
Nowadays, with intense concern for the preservation of the environment and with the advent of biotechnological innovation, there is a growing interest in identifying, quantifying and qualifying agroindustrial residues, in order to develop new products for their use. In this context, the residues generated in the production of beer (brewery spent grain) and also the industry of macauba (residual pulp), are shown to be promising because they present essential nutrients, such as fibers and active biomolecules. This work aimed to evaluate the potential use of these residues as raw materials for the production of flours, followed by their use for the manufacture of cookie. The physico-chemical composition and technological properties of Macaúba (MC), pure malt (PM) and mixed (MS) flour were determined. It was elaborated cookies using the flours to replace wheat flour on three levels: 5%, 10%, and 15%. The physical and technological characteristics of the cookies were analyzed. The flours presented a composition that makes them materials of interest for the production of new food products with high nutritional value, mainlly fibers. The incorporation of macauba cake (MC), pure malt (PM) and mixed (MS) flours alters the quality of biscuits and their technological and sensorial characteristics.